ANALYSIS OF ENVIRONMENTAL POLLUTION POLICIES DUE TO ECONOMIC AND TECHNOLOGICAL DEVELOPMENTS: - Risyaldi Rahmattullah (Journal Education and Government Wiyata, 2023)
Environmental pollution is a consequence of economic and technological developments that exceed the tolerance of ecosystems, increasing the amount of pollutants in the air, water and soil. This article discusses the negative impacts of environmental pollution, such as ecosystem damage, poor health, and loss of natural resources. Contributing factors include greenhouse gas emissions, industrial waste, and air and water pollution. The literature review provides an insight into the concept of pollution and environmental policies implemented by the government. The results and discussion describe the types of pollution (air, water, land) and the factors that cause them, with a focus on their impact on human health. SWOT analysis identifies strengths, weaknesses, opportunities and threats in overcoming environmental pollution. Several government regulations are also described as efforts to control pollution. Ways to overcome the impacts of pollution include the 4R principles, reforestation, bioremediation, land rehabilitation and coastal reclamation. Public awareness, waste management, environmentally friendly technology and government policies are also considered important. The SWOT analysis highlights challenges in regulatory enforcement, global coordination, and dependence on polluting industries. The conclusion emphasizes the urgency of awareness and collective action to overcome environmental pollution. This article details health implications such as respiratory disease, eye irritation, and risk of premature birth. Prevention efforts include public awareness, waste management, clean technology, and international collaboration. The threat of climate change and resistance to change were identified as barriers. In conclusion, decisive action is needed to protect the environment and human health.